THE INFLUENCE INTELLECTUAL CAPITAL, ASSET GROWTH, AND BANKING FINANCIAL PERFORMANCE - Kurnia Heriansyah; Irma Sari Permata; Sri Irviati Wahyoeni (Sean Institute, 2023)
Successful companies are those that continue to innovate, utilize new technology and emphasize employee skills and knowledge. Banking performance does not depend on physical assets alone but on intangible assets or Intellectual Capital. The growth of assets in banking, especially customer trust in the form of third party funds which are then channeled in the form of credit and investment, which can increase banking income. This research aims to prove and analyze the influence of intellectual capital and asset growth on banking financial performance at BUMN Banks, BPD BJB-Banten, and BPD East Java. The dependent variable is banking financial performance as measured by Return On Assets for the 2015-2019 period (before the Covid 19 pandemic), while the independent variables are intellectual capital and asset growth. This quantitative research method is expanatory with secondary data obtained from banking annual reports. The research results prove that intellectual capital and asset growth have a positive effect on the financial performance of state-owned banks and BPDs for the period 2015 to 2019. Banking performance assessment also uses the business performance indicator IC VAICTM performance score ranking, which explains BNI, BRI, Bank Mandiri, and BPD East Java is in the Top performers category. BPD Banten-West Java was included in Top performers in 2015 and 2019, while in 2016, 2017, 2018 it was included in Good performers. BTN in 2019 was in the Bad performers category, while in 2015-2018 it was in the Top performers category.